Analisis Tingkat Kebangkrutan Dengan Menggunakan Metode Altman Z-Score, Springate Dan Internal Growth Rate Pada Pt Bentoel Internasional Investama Tbk - Juhli Edi Suranta Simanjuntak; Meri Aziana; Tommy Munaf (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to determine how the level of bankruptcy at PT Bentoel Internasional Investama Tbk from 2016 to 2020 using the Altmatn Z-Score, Springate, and Internal Growth Rate methods. Companies, investors and creditors are expected to consider the results of this analysis. The type of research used in this research is descriptive research, in predicting bankruptcy the researcher uses multivariate analysis. This study uses secondary data from the company's financial statements listed on the Indonesia Stock Exchange. To measure financial performance, researchers analyzed the ratios contained in the three models.The results of the analysis of the company's bankruptcy rate using the Altman Z-Score method in 2016 were the company was in the